Analisis Nilai-Nilai Pendidikan Pada Novel A+ Karya Ananda Putri Sebagai Bahan Ajar Pembelajaran Sastra Di SMA - Naufal, Muji Zain; Apriyanto, Ade; Mudiasih, Maylani (BRILIANT: Jurnal Riset dan Konseptual, 2024)
The significance of education is a crucial value that is both instructive and practical for one's lifetime. Teachers can impart these principles to their students. Presently, there is a growing consensus that the importance of education should be given top priority, as the moral and ethical growth of pupils is being compromised by the prevalence of juvenile delinquency among them. The significance of education in daily life can be elucidated through literary compositions, specifically novels. This research was conducted to analyze the educational qualities depicted in the novel "A+" by Ananda Putri and subsequently utilize these findings to develop literary learning modules for high school students. The research methodologies employed include qualitative methods and research and development (R&D). The research findings indicate that the novel "A+"  encompasses 14 educational values, namely 1) religious, 2) honest, 3) tolerance, 4) discipline, 5) hard work, 6) democratic, 7) curiosity, 8) appreciates achievements, 9) friendly, 10) loves peace, 11) likes reading, 12) social care, 13) responsible, 14) independent. Moreover, these findings were utilized as substitute instructional resources in the shape of educational value learning modules for twelfth-grade high school students. After undergoing validation by multiple experts, this training material achieved a score of 79.88%.